Public-Private Partnerships to Reform Urban Water Utilities in Western and Central Africa - Fall, Matar; Marin, Philippe; Locussol, Alain; Verspyck, Richard (World Bank, Washington, DC, 2012)
Western and Central Africa have lengthy experience with public-private partnerships (PPPs), both for water supply and for combined power and water supply utilities. Cote d'Ivoire's successful PPP dates from 1959, and, over the last two decades, as many as 15 out of 23 countries in the region have experimented with PPPs. Eleven PPPs are studied here, and detailed performance indicators are reported for six large cases-Cote d'Ivoire, Senegal, Niger, Mali, Burkina Faso, and Gabon. These PPPs all have had at least four years of private operation. Through its successes and failures, the Western and Central African experience offers interesting lessons for other developing countries on how to improve the quality of urban water supply services, increase the efficiency of operations, and establish the financial credibility of the sector.